GABAergic mechanisms of the lateral parabrachial nucleus on sodium appetite - de Oliveira, Lisandra B.; Callera, João Carlos [UNESP]; De Luca, Laurival A.; Colombari, Debora S. A.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2007)
GABAergic activation in the lateral parabrachial nucleus (LPBN) induces sodium and water intake in satiated and normovolemic rats. In the present study we investigated the effects of GABA(A) receptor activation in the LPBN on 0.3 M NaCl, water, 2% sucrose and food intake in rats submitted to sodium depletion (treatment with the diuretic furosemide subcutaneously + sodium deficient food for 24 h), 24 h food deprivation or 24 h water deprivation. Male Holtzman rats with bilateral stainless steel cannulas implanted into the LPBN were used. In sodium depleted rats, muscimol (GABA(A) receptor agonist, 0.5 nmol/0.2 mu/l), bilaterally injected into the LPBN, produced an inconsistent increase of water intake and two opposite effects on 0.3 M NaCl intake: an early inhibition (4.3 +/- 2.7 versus saline: 14.4 +/- 1.0 ml/15 min) and a late facilitation (37.6 +/- 2.7 versus saline: 21.1 +/- 0.9 ml/180 min). The pretreatment of the LPBN with bicuculline (GABA(A) receptor antagonist, 1.6 nmol) abolished these effects of muscimol. Muscimol into the LPBN also reduced food deprivation-induced food intake in the first 30 min of test (1.7 +/- 0.6 g versus saline: 4.1 +/- 0.6 g), without changing water deprivation-induced water intake or 2% sucrose intake in sodium depleted rats. Therefore, although GABAA receptors in the LPBN are not tonically involved in the control of sodium depletion-induced sodium intake, GABAA receptor activation in the LPBN produces an early inhibition and a late facilitation of sodium depletion-induced sodium intake. GABAA activation in the LPBN also inhibits food intake, while it consistently increases only sodium intake and not water, food or sucrose intake. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: sodium depletion; sodium intake; thirst; food intake; sucrose intake; muscimol